(untitled) - Lin, Yi-Bing (Indianapolis, IN., 2005)
Looks at the number one advancement currently emerging from 3GPP (Third Generation Partnership Project) in global wireless growth: the development of wireless applications based only on the Internet Protocol (IP) which drives the Web. Focusing on the emerging all-IP core network and applications, this book covers. 3G and shows how the all-IP core network can be developed and how applications can be created. Contains review questions and their solutions at the end of each chapter, all of which have been tested, as well as models for implementation
Mạng không dây và di động
Keywords: Wireless communication systems,Mobile communication systems,Computer network protocols